Comparison of Multilayer Transparent Wood and Single Layer Transparent Wood With the Same Thickness - Wu, Yan; Wang, Yajing; Yang, Feng (Frontiers in Materials, 2021)
In this paper, poplar was used as raw material, sodium chlorite was used to delignify it in acidic environment, and then epoxy resin was vacuum impregnated in the delignified wood template to prepare transparent wood. Moreover, in order to imitate the lamination method of plywood, the multilayer transparent wood was prepared by means of staggered vertical lamination. The purpose of this paper is to study the physical and chemical properties of multilayer transparent wood, and to explore the application potential of multilayer transparent wood as a new material by comparing with single layer transparent wood with the same thickness. The weight of wood components in the transparent wood prepared in this experiment accounts for about 30–45% of the weight of composite materials. Scanning electron microscopy (SEM) measurements, Fourier transform attenuated total reflection infrared spectroscopy (ATR-FTIR) characterization, weight gain measurements, UV transmittance measurements, color difference measurements, water contact angle measurements and mechanical properties measurements were used to study. The results showed that as the thickness of the transparent wood increased, the cracks between the resin and the wood cell wall increased, and the interface showed an uneven state. In the case of the same thickness, the multilayer transparent wood was made by laminating transparent wood sheets, with fewer internal cracks and smooth interfaces. Its light transmittance is better than single layer transparent wood. Moreover, compared with single layer transparent wood with the same thickness, the lightness of multilayer transparent wood decreased, and tended to yellow and red. Due to the removal of lignin, the tensile strength of transparent wood decreased during the preparation process. However, it can be seen from the mechanical strength test that the tensile strength of multilayer transparent wood is much higher than that of single layer transparent wood. To a certain extent, multilayer transparent wood can improve the mechanical strength of transparent wood. To conclude, multilayer transparent wood is a kind of natural transparent material with large thickness, good light transmission and excellent mechanical properties, and it has a good development prospect.